Contribution of dietary snacking behaviours to discretionary energy intake and anthropometric measures in Australian adults: A comparison using an objective vs subjective definition for snacking. Issue 2 (3rd November 2020) - Fayet‐Moore, Flavia; McConnell, Andrew; Petocz, Peter; Cassettari, Tim; Tuck, Kate; Blumfield, Michelle; Warner, Molly; Marshall, Skye
Abstract: Aim: There is limited information on the snacking behaviour of Australian adults, and the role of snacking in the diet may depend on how it is defined. This study aimed to compare the dietary snacking behaviours and associated nutritional intake and body composition in Australian adults, using an objective vs a subjective definition for snacking. Methods: Cross‐sectional data were analysed from the 2011 to 2012 National Nutrition and Physical Activity Survey (n = 8361, 19+ years). Objective snacking was defined based on time of day between main meals. Subjective snacking was self‐reported by participants. Results: Using the objective definition, 88.2% of adults were snack consumers; where snacking contributed 20.0% (SD 20.0%) of total daily energy intake and 27.0% (SD 31.4%) of total daily discretionary energy. 41.3% (SD 37.1%) of snacking energy intake came from discretionary foods. Using the subjective definition, 98.5% of adults were snack consumers, where discretionary foods contributed 52.6% (SD 35.2%) of all snacking energy. The proportion of objective and subjective snacking energy from discretionary foods did not differ across body mass index groups. Conclusions: Objective snacking energy contributed more to core food groups than discretionary, was not associated with anthropometric measures, and contributed less to total discretionary energy than the evening meal. When snacking was defined subjectively, more than half of snacking energy was discretionary, suggesting that adults are more likely to perceive discretionary foods as snacks. Differences between snacking definitions means that associations between self‐reported snacking and diet or health outcomes, should be interpreted with caution.